Novel transition metal modified layered phosphate for reducing the fire hazards of PA6. (January 2023) - Qian, Xiaodong; Shi, Congling; Wan, Mei; Jing, Jingyun; Che, Honglei; Ren, Fei; Li, Jian; Yu, Bin
Abstract: To date polyamide 6 (PA6) have been widely applied in many different fields such as mechanical parts, electronic and electrical products. Nevertheless, the inherent flammability of PA6 threaten the safety of life and properties, restricting its comprehensive applications. In this work, three types of metal phosphate modified layered melamine phytate hybrids are designed and prepared by supramolecular self-assembly technology, and the hybrids are incorporated into glass fiber reinforced PA6. The flame retardancy as well as smoke suppression properties of the composites with different transition metal modified flame retardants are compared and investigated. The results of cone calorimeter test indicate that the metal phosphate modified layered melamine phytate based composites can reduce both the peak heat release (pHRR, <32%) and total heat release (THR, <28%) compared to those of pure glass fiber reinforced PA6; the smoke and toxic volatiles productions are also reduced significantly, and Cu phosphate modified layered melamine phytate hybrids (PA-MEL-Cu) perform better than other flame retardants on suppressing the heat release and smoke releasing of PA6. The mechanism investigations demonstrate that the improved fire safety properties of PA6 composites are attributed to the physical barrier effect and the selective catalysis effect of transition metal during the combustion. This strategy not only prepares metal phosphate modified layered melamine phosphate by in-situ precipitation, but also promotes the promising potentials of melamine phosphate in the flame retardant application of polymer composites. Graphical abstract: Image 1 Highlights: Three metal phosphate modified layered melamine phytate hybrids are synthesized by supramolecular self-assembly technology. Metal phosphate modified layered melamine phytate based composites can significantly reduce the release of heat and smoke. The improved fire safety properties are due to physical barrier effect and selective catalysis effect of transition metals.